Afrofuturist Responses to State Violence - Caren Holmes (Janeway JS, 2020)
Afrofuturist writing is a vehicle through which authors reverse, disrupt, confront, disappear or amplify contemporary manifestations of state violence. This article investigates two Afrofuturist short stories written by American diasporic authors and explores how they imagine possibilities for responding to violence produced at the hands of the state. Using conceptions of Necropolitics, racial trauma, rage, and colonial pathologization, the article considers ‘alien’ and ‘beyond human’ responses to police brutality, criminalization, destitution and incarceration in the United States. Afrofuturist writing ultimately does not conceive of an end to the ‘carceral continuity’ of the United States but envisages futuristic resilience to and mutating strategies of resistance.
Keywords: Musical fusion; gender fluidity; Balinese gamelan; string quartet